Traditional medicine in the Tradiciones peruanas by Ricardo Palma - Beltrán Simón, Brigith Anabeli (2019)
This article will analyze the traditions «Los polvos de la condesa» and «El abad de Lunahuaná», texts where Ricardo Palma explains the ancient and traditional natural ways of how a disease was treated with the quinine, the plantain and the hoja santa or sacred leaf.